Overlap or breakthrough? exploration of the academic buoyancy structure in Chinese EFL learners. - Tao Zeng; Ke Zhong; Wanting Wang (PLoS ONE)
Academic buoyancy, recognized as a key component of positive personality traits in learning, has garnered significant attention. However, most research on buoyancy is limited to general educational contexts, lacking a comprehensive theoretical framework that poses challenges in evaluating buoyancy's impact on learners within the domain of second language acquisition (SLA). This study seeks to bridge this gap by investigating academic buoyancy within the realm of foreign language learning, specifically among university students in mainland China studying English as a foreign language (EFL). The study comprises two phases, with a total of 632 EFL participants. In the initial phase, a 32-item scale was tailored to the present study, drawing on scales from previous buoyancy-related research. Item analysis and exploratory factor analysis were subsequently conducted with a sample of 209 students. The phase retained 21 measurements and identified three main components of buoyancy: sustainability (the ability to persist despite difficulties), goal-orientedness (the focus on achieving specific learning objectives), and controllability (the perception of managing learning challenges). In the second phase, the refined questionnaire was administered to an additional 423 students, and the data underwent confirmatory factor analysis. A reliable 12-item scale was obtained that accurately reflects the identified components of academic buoyancy. By elucidating the structure of buoyancy, this study offers valuable empirical insights that can guide pedagogical strategies and strengthen learner buoyancy in language learning contexts. The findings contribute to the broader discourse on positive personality traits in education, highlighting the importance of fostering buoyancy in language learners to support their academic success.